Draft Genome Sequence of Sphingopyxis sp. Strain MWB1, a Crude-Oil-Degrading Marine Bacterium - Kim, Jonghyun (Genome Announc, 2014)
Sphingopyxis sp. strain MWB1, which is capable of degrading crude oil, diesel, and kerosene, was isolated from crude oil–contaminated seashore in Tae-an, South Korea. Here, we report the draft genome sequence of this strain, which comprises 3,118,428 bp with a G+C content of 62.85 mol%.